Look at the weather - Teckentrup, Britta (Owlkids Books, 2018)
"A meditative, immersive take on the weather around us. Sophisticated nonfiction picture book with informational content. Illustrated with striking atmospheric paintings. Includes calls to action for the reader, inviting them to observe and inquire about the outdoors. Through four chapters-sun, rain, ice and snow, and extreme weather-this book explores different weather phenomena, from rainbows and sunsets to clouds, frost, and rainstorms. Evocative paintings convey the sheer power of weather, while lyrical text captures the richness of our natural environment. The book takes an inspiring tone rather than an exhaustive, factual one. The book explicitly makes the link between extreme weather, climate change, and human activity, and poses questions often, inviting young readers to observe and inquire about their own environment or to imagine other ones"--